Rydberg states and Molecular Photo- Absorption Spectrum of Vinyl Chloride - Anwar Mustafa Ezzat Al-Faydhi (مجلة التربية والعلم, 2007)
Abstract In this work, a comprehensive study of the molecular spectroscopy of vinyl chloride is reported. A high resolution VUV photo absorption spectrum of vinyl chloride has been measured using a synchrotron radiation in the range (5 - 11) eV (115 > λ > 250) nm. The excited Rydberg states of vinyl chloride were calculated using a software program. The photolysis has also been investigated to give an estimate of the life time in the atmosphere.